The Implementation of Mamdani Fuzzy Logic Control on a Hexapod Robot as a Guide for Visually Impaired People - Mohamad Agung Prawira Negara; Fikri Mulyadi; Ali Rizal Chaidir; Khairul Anam (Jurnal Elektronika dan Telekomunikasi, 2024)
The constraints faced by visually impaired individuals have spurred various human-created innovations to aid them. One such innovation is employing robots as guides for the blind. Numerous studies have delved into utilizing robots as guides for visually impaired individuals. Nevertheless, these robots still encounter limitations, particularly in navigating rough and uneven terrain. To tackle this issue, there's a necessity for a hexapod robot capable of traversing uneven surfaces more effectively than wheeled robots. The hexapod robot developed in this research is an autonomous robot that employs fuzzy logic as its control method. The resultant hexapod robot has showcased outstanding performance, attaining a 100% success rate in navigating the specified path and demonstrating a reliability of 79.78%.